Wild laughter: how to read the picture books of Mauric Sendak - Escrig Aparicio, José Antonio (Ondina - Ondine, 2020)
The work of Maurice Sendak condenses a variety of central themes (humor, violence, controversy, sexuality…) that sometimes has constrained the aesthetic appreciation of it. A formalist or moralizing approach failed to establish the common root of this phenomena and turns Sendak away from the artistic chain (Hieronimus Bosch, William Blake, the illustrators of German Expressionism…) to which he belongs. This paper explores the common root of Maurice Sendak’s imagination on the basis of “grotesque”, a key concept of contemporary aesthetic studies about laughter. Key Words: Maurice Sendak, laughter, grotesque, picture book, childhood